MONITORING SETORAN SATKER PENGGUNA DANA PENERIMAAN NEGARA BUKAN PAJAK - Sumantri, Joko (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2019)
Monitoring the transfer of money to the state treasury and the use of PNBP funds is needed so that the funds allocated are right on target according to the provisions. This study tries to determine the suitability of the implementation of the monitoring task of PNBP user satker deposits by the Regional Office of the Directorate General of Treasury with applicable regulations. Using the descriptive research method, it was found that the implementation of the monitoring task of PNBP user satker deposits in the Regional Office of the Directorate General of Treasury of West Java and DKI Jakarta was still different in their implementation. In addition, there is still a need to fulfill the needs and expand the authority of the Regional Office of the Directorate General of Treasury.